Child abuse : prevention through understanding - Daly, Evin M.; Wright, John E. (Parker Publishing, 2017)
Child Abuse: Prevention through understanding is the definitive guide to understanding every facet of child abuse--physical, emotional, and sexual; and neglect. Providing an in-depth look at each type of abuse, including descriptions of often-unrecognized signs, illustrations that clarify complex concepts, and a comprehensive glossary of terms, Child Abuse: Prevention through understanding offers a must-read, essential guide for parents, child caregivers, teachers, students, law enforcement, volunteers, caseworkers, first responders--anyone who has contact with children. It is an indispensable resource and reference source for anyone who cares about children and child protection. This book provides the information that we as individuals and as a society should know--and understand--so that child abuse can be combatted effectively. In addition, this book offers extensive, clear, and detailed information about the common connection between child abuse, domestic abuse, and domestic violence.
Child abuse : a (very) short history -- About child abuse -- Physical child abuse -- Sexual child abuse -- Emotional child abuse -- Neglect -- Domestic violence -- Quick facts : child abuse-the short version.
Includes glossary.
Includes bibliographical references (pages 287-320) and index.
Keywords: Child abuse; Family violence; Child Abuse; Enfants -- Violence envers; Violence familiale; Child abuse; Family violence